Ethnic Differences in Informal Caregiving After Stroke. Issue 12 (December 2021) - Morgenstern, Lewis B.; Hollenhorst, Cecilia N.; Gallo, Linda C.; Hsu, Chia-Wei; Kim, Sehee; Gibbs, River; Case, Erin; Lisabeth, Lynda D.
Abstract : Background and Purpose: Informal (unpaid) caregiving usually provided by family is important poststroke. We studied whether the prevalence of informal caregiving after stroke differs between Mexican Americans (MAs) and non-Hispanic Whites (NHWs). Methods: Between October 2014 and December 2018, participants in the BASIC (Brain Attack Surveillance in Corpus Christi) project in Nueces County, Texas, were interviewed 90 days after stroke to determine which activities of daily living they required help with and whether family provided informal caregiving. Ethnic differences between MAs and NHWs were determined by logistic regression. The logistic models were stratified by formal (paid) care status. Odds ratios (95% CIs) are reported with NHW as the referent group. Fisher exact tests were used to assess the association of ethnicity with relationship of caregiver and with individual activities of daily living. Results: Eight hundred thirty-one patients answered the caregiving questions. Of these, 242 (29%) received family caregiving (33% of MAs and 23% of NHWs), and 142 (17%) received paid caregiving (21% of MAs and 10% of NHWs). There were no ethnic differences in stroke severity. In logistic regression analyses, among those without formal, paid care, MAs were more likely to have informal caregiving (odds ratio, 1.75 [95% CI, 1.12–2.73]) adjusted for age, National Institutes of Health Stroke Scale, prestroke modified Rankin Scale, and insurance. No ethnic differences in informal care were found among those who had formal care. There were no differences between ethnic groups in which family members provided the informal care. MAs were more likely to require help compared with NHWs for walking ( P <0.0001), bathing ( P <0.0001), hygiene ( P =0.0012), eating ( P =0.0004), dressing ( P <0.0001), ambulating ( P =0.0304), and toileting ( P =0.0003). Conclusions: MAs required more help poststroke than NHWs for assistance with activities of daily living. MAs received more help for activities of daily living through informal, unpaid caregiving than NHWs if they were not also receiving formal, paid care. Efforts to help minority and low-resource populations provide stroke care are needed. Abstract : Supplemental Digital Content is available in the text.